Famílias e domínios proteicos associados com a evolução da eussocialidade em Hymenoptera - Maycon Douglas de Oliveira (2022)
The order Hymenoptera consists of the insects commonly known as bees, ants, wasps and sawflies, critical for the maintenance of the diversity and homeostasis of ecosystems (e.g., pollination in rural and wild environments and dispersion of native seeds). The Hymenoptera possess the largest number of independent gains and losses of eusociality among metazoans. The search for homologous regions significantly associated with the phenotype of eusociality through the analysis of gene families and protein domains may offer important information for the molecular understanding of this phenomenon. However, species-related data are not independent since they share common ancestors. A plethora of comparative methods were developed in the last decades in order to enable the search for associations between data derived from phylogenetically-related organisms, incorporating their phylogeny as an additional parameter for the models. In the present work, we integrated phylogenetic, phenotypic and genomic data in order to build phylogeny-aware statistical models and search for homologous groups whose count is significantly associated with eusociality in 62 high-quality annotated Hymenoptera genomes representative of species classified as eusocial or solitary. From a total of 2,045,867 homologous regions belonging to 9,662 unique protein domains and families gathered from those genomes, six are significantly associated with the presence/absence of eusociality and showcase a rich functional diversity. We highlight THAP4, a gene that seems to be associated with adaptations to life in low oxygen environments and is expanded in ants, who build underground nests, and the gene Snx14, involved in embryonic development and energy storage and that is only present in eusocial bees. We also observed genes with scarce functional characterization that represent interesting targets for functional evaluation. Importantly, all of those genes are absent in a number of Hymenoptera species, which suggests that they are not essential. In conjunction, these results provide an important starting point for knockout and knockdown-based functional analyses of those genes in Hymenoptera, devising a larger comprehension of their role in the control and evolution of eusociality.